FAKTOR PENYEBAB TERJADINYA KARIES GIGI PADA SISWA SD SAMBIROTO 02 SEMARANG - Erni Mardiati; Salikun Salikun; Iman Supardan (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2017)
TITLEThe causative factors of dental caries in students of SD Sambiroto 02 SemarangABSTRACTTooth is part of the masticatory apparatus of the digestive system in the human body. Based on the preliminary study found 45% of students of Sambiroto 02 Elementary School have fixed dental caries, 15% had dental caries milk and 40% have bad oral hygiene. The main problem of oral health in students of Sambiroto 02 Elementary School is dental caries. Dental caries is an infectious disease caused by demineralization of enamel and dentine that is closely related to the consumption of cariogenic foods. Generally, children entering school age have a high risk of caries. This study aims to determine the factors that cause dental caries in students at Sambiroto 02 Elementary School Semarang.This type of research is quantitative descriptive case study method. Data retrieval is done by checking caries (DMF-T) OHIS, Plaque Index, pH Saliva, Viscosity Saliva, Saliva Hydration, as well as the questionnaire for behavioral variables (knowledge, attitudes, practices). Priority problems using odd ratio test showed that the factors causing the most dominant is the practice (p value = 65.0), OHIS (p value = 20.43), and plaque index (p value = 17.0).The results showed that the factor of the practice 50% of respondents with bad category, 62% of respondents with OHIS bad category, and 62% of respondents who had a plaque with bad category. The problem solving are a revitalization program UKGS, cariogenic diet control, brushing teeth together, topical application fluoride / CPP-ACP, dental health education, training of cadres, and filling cavities. Advices to students are expected to increase knowledge as a basis for understanding the attitude and behavior are good on prevent dental care that are not easily affected by caries, and suggestions presented to the teachers to always give motivation to students to always maintain dental health. Keywords : Caries, students Primary School Sambiroto.